2020
DOI: 10.3390/nu12113526
|View full text |Cite
|
Sign up to set email alerts
|

Administration of an Intravenous Fat Emulsion Enriched with Medium-Chain Triglyceride/ω-3 Fatty Acids is Beneficial Towards Anti-Inflammatory Related Fatty Acid Profile in Preterm Neonates: A Randomized, Double-Blind Clinical Trial

Abstract: Intravenous administration of pure soybean oil emulsions high in linoleic acid may lead to inflammation and lipid peroxidation in preterm neonates. We aimed to investigate the effects of a medium-chain triglyceride (MCT)/ω-3 polyunsaturated fatty acid (PUFA)-enriched intravenous fat emulsion (IVFE) on plasma fatty acid (FA) profile and serum interleukin-6 (IL-6) in preterm neonates. In this double-blind randomized study, 92 preterm neonates (gestational age < 32 weeks, birth weight < 1500 g) were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Also, the balance between metabolites of n-3 and n-6 PUFAs seems to be important in pregnancy maintenance and have a significant role in cervical dilatation and initiation of labour [ 32 ]. In randomized, double-blind clinical trials carried out in preterm neonates, the administration of medium-chain triglyceride/n-3 PUFA-enriched intravenous fat emulsion changed the fatty acid profile consistent with an attenuated inflammatory response [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the balance between metabolites of n-3 and n-6 PUFAs seems to be important in pregnancy maintenance and have a significant role in cervical dilatation and initiation of labour [ 32 ]. In randomized, double-blind clinical trials carried out in preterm neonates, the administration of medium-chain triglyceride/n-3 PUFA-enriched intravenous fat emulsion changed the fatty acid profile consistent with an attenuated inflammatory response [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no significant difference in the daily dose of ursodiol According to the literature, giving preterm neonates fish oil-containing ILEs is linked to reduced inflammatory response. 18 In addition to reducing the supply of potentially oxidative, inflammatory/immunosuppressive, and prothrombotic ω-6 fatty acids, the incorporation of fish oil also brings about biological effects and appears to decrease the risk of infections and the duration of hospital or intensive care unit stay. 10,[19][20][21] Eicosapentaenoic acid and docosahexaenoic acid, as direct precursors of powerful specialized proresolving mediators, possess favorable bioactivities with established mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, giving preterm neonates fish oil–containing ILEs is linked to reduced inflammatory response 18 . In addition to reducing the supply of potentially oxidative, inflammatory/immunosuppressive, and prothrombotic ω‐6 fatty acids, the incorporation of fish oil also brings about biological effects and appears to decrease the risk of infections and the duration of hospital or intensive care unit stay 10,19–21 .…”
Section: Discussionmentioning
confidence: 99%
“…The ratios ω-6 and ω-3 should be between 2:1 and 4:1, and some health teachers advocate even lower ratios. Studies have shown that a 2-3: 1 ratio between ω-6 and ω-3 helps reduce inflammation in patients with rheumatoid arthritis, a ratio of 5: 1 has a beneficial effect on asthma patients, and the ratio is 10: 1 Has a negative effect: the ratio 2.5: 1 has a reduced effect on the proliferation of rectal cells in patients with colorectal cancer, but the ratio 4: 1 has no effect (Papandreou et al, 2020;Zong et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%